Worldwide epidemiologic factors in pemphigus vulgaris and bullous pemphigoid - Rosi-Schumacher, Mattie; Baker, John; Waris, James; Seiffert-Sinha, Kristina; Sinha, Animesh A. (Frontiers in Immunology, 2023)
Autoimmune blistering diseases such as bullous pemphigoid (BP) and pemphigus vulgaris (PV) are complex, multifactorial, and polygenic diseases, whose exact pathogenesis is difficult to pinpoint. Research aimed at elucidating the associated epidemiologic risk factors of these two diseases has been hampered by their rare disease status. Further, a lack of centralization and standardization of available data makes the practical application of this information challenging. In order to collate and clarify the available literature we comprehensively reviewed 61 PV articles from 37 different countries and 35 BP articles from 16 different countries addressing a range of disease relevant clinical parameters including age of onset, sex, incidence, prevalence, and HLA allele association. The reported incidence of PV ranged from 0.098 to 5 patients per 100,000 people, while BP ranged from 0.21 to 7.63 patients per 100,000. Prevalence of PV ranged from 0.38 to 30 per 100,000 people and BP ranged from 1.46 to 47.99 per 100,000. The mean age of onset in patients ranged from 36.5 to 71 years for PV and 64 to 82.6 years for BP. Female-to-male ratios ranged from 0.46 to 4.4 in PV and 1.01 to 5.1 in BP. Our analysis provides support for the reported linkage disequilibrium of HLA DRB1*0402 (an allele previously shown to be associated with PV) and DQB1*0302 alleles in Europe, North America, and South America. Our data also highlight that HLA DQB1*0503 (also known to be associated with PV) appears in linkage disequilibrium with DRB1*1404 and DRB1*1401, mainly in Europe, the Middle East, and Asian countries. The HLA DRB1*0804 allele was only associated with PV in patients of Brazilian and Egyptian descent. Only two HLA alleles were reported as associated with BP more than twice in our review, DQB1*0301 and DQA1*0505. Collectively, our findings provide detailed insights into the variation of disease parameters relevant to PV and BP that can be expected to inform future work aimed at unraveling the complex pathogenesis of these conditions across the globe.